Body condition and fuel deposition patterns of calidrid sandpipers during migratory stopover - Choi, Chiyeung; Gan, Xiaojing; Ma, Qiang; Zhang, Kejia; Chen, Jiakuan; Ma, Zhijun (Ardea, 2009)
We compared seasonal variations in body condition and fuel deposition patterns of five calidrid sandpipers at Chongming Dongtan (eastern China), a stopover site in the East Asian-Australasian Flyway. We tested the hypothesis that long-distance migrants show different body condition and fuel deposition patterns relative to those undertaking short-distance flights. Results indicated that the body condition and fuel deposition patterns of the sandpipers varied between the northward and southward migration seasons and between ageclasses. Great Knots Calidris tenuirostris and Red Knots Calidris canutus migrate southwards on a long-distance nonstop flight from Chongming Dongtan to northwest Australia, while covering on the return flight a relatively short-distance between Chongming Dongtan and the north Yellow Sea region. Both species attained a significantly higher body condition at Chongming Dongtan during the southward than northward migration. Moreover, they showed a significant increase in body condition at Chongming Dongtan during northward migration stopover, which we see as a recovery from the long flight from Australia. In contrast, Red-necked Stints Calidris ruficollis and Long-toed Stints Calidris subminuta, employing series of relatively short-distance flights during migration, indicated no significant difference in departure body condition at Chongming Dongtan between seasons, nor significant increase in body condition during either migration stopover. Dunlins Calidris alpína on the other hand, showed a significantly higher body condition during northward than southward migration stopover, most likely in anticipation of the longer travelling distance after leaving Chongming Dongtan during northward migration. This study confirms that the body condition and fuel deposition patterns among shorebird species that undertake long-distance nonstop flights are different from those that undertake series of short-distance flights, suggesting that the comparison of body condition and fuel deposition patterns of calidrid sandpipers can be an important tool to understand their migration strategies.